Institutional Theory and International Entrepreneurship: A Review - Steinhauser, Vivian; da Rocha, Angela; de Oliveira Paula, Fábio (Internext, 2022)
Purpose: To review the literature that uses institutional theory to examine the internationalization of smaller and entrepreneurial firms, covering the period from January 1, 2008 to September 30, 2020. Method: The bibliometric review uses the bibliographic coupling technique and content analysis. Main Findings: The literature was divided in three periods using bibliometric techniques, and the main themes examined in each period were identified and analyzed qualitatively. Relevance /Originality: Only one previous literature review examined the same issue addressed in this paper, but only covered articles published up to 2008 (Szyliowicz & Galvin, 2010). Theoretical Contributions: The study uncovers the thematic structure of the field throughout the period examined and suggests issues for future research.